Role of Foreign-Born Status on Suicide Mortality in Spain Between 2000 and 2019: An Age-Period-Cohort Analysis - Martínez-Alés, Gonzalo; Gimbrone, Catherine; Rutherford, Caroline; Keyes, Katherine; López-Cuadrado, Teresa (International Journal of Public Health, 2022)
Objectives: To examine recent age-period-cohort effects on suicide among foreign-born individuals, a particularly vulnerable sociodemographic group in Spain. Methods: Using 2000-2019 mortality data from Spain’s National Institute of Statistics, we estimated age-period-cohort effects on suicide mortality, stratified by foreign-born status (native- vs. foreign-born) and, among the foreign-born, by Spanish citizenship status, a proxy for greater socioeconomic stability. Results: Annual suicide mortality rates were lower among foreign- than native-born individuals. There was heterogeneity in age-period-cohort effects between study groups. After 2010, suicide mortality increased markedly among the foreign-born – especially for female cohorts born around 1950, and slightly among native-born women – especially among female cohorts born after the 1960s. Among native-born men, suicide increased linearly with age and remained stable over time. Increases in suicide among the foreign-born were driven by increases among individuals without Spanish citizenship – especially among cohorts born after 1975. Conclusions: After 2010, suicide in Spain increased markedly among foreign-born individuals and slightly among native-born women, suggesting an association between downstream effects of the 2008 economic recession and increases in suicide mortality among socioeconomically vulnerable populations.